Effect of Soaking Maize Seeds with Nano-Iron Fertilizer on Germination, Yield and Animal’s Physiological Characteristics toxicity - Zainab A. Hassan; Ahmed Ch. Al-Fahad; Saddam H. Cheyed (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2025)
A field experiment was conducted during the spring season of 2021 in the Experimental field of the College of agricultural engineering sciences - university of Baghdad with the aim of knowing the effect of soaking seeds with nano-iron at concentrations of (0, 50, 100 and 150 mg L-1) on seed viability, field emergence, grain yield and  components and grain Iron content  The results showed significant increase in germination indicators, seedling field emergence, grain yield and its components accompanied by an increase of nano-iron concentrations up to 150 mg L-1. Moreover, the results of seed Iron content showed accumulated of toxic level of Nano-Iron in seeds. The toxicity includes imbalance liver’s functions, kidneys and oxidative imbalance of laboratory mice.